The Flat Earthen Roofs of Traditional Kemaliye (Eğin) Houses: Unique and Authentic Features to Preserve in Anatolia - Taskent Bagci, Begum; Ciftci, Aynur (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Flat earthen roofs are a type of roof covering seen in Anatolia and elsewhere around the world in low rainfall areas. Kemaliye is a traditional Anatolian settlement where these flat roofs can still be seen. The site was added to the UNESCO World Heritage Tentative List in 2021. What makes the local architecture unique is the construction of the earthen roofs with two distinctive features: roof coverings with stone upper layers and four different types of eaves. Unfortunately, since the 1950s, due to the lack of maintenance caused by migration and population loss, flat roofs have been covered with inappropriate additional timber structure roofs and metal sheets. Therefore, Kemaliye town and its traditional houses have partially lost their authentic character. This article, based on a master's thesis prepared in the field of architectural conservation, is also the output of a TUBITAK research project.
Keywords: Erzincan; Kemaliye; Anatolia; traditional house; flat-earthen roof; conservation; Architecture